Effects of injection of hydrolysis plasma protein solution on the antioxidant properties in porcine M. Longissimus Lumborum. Issue 1 (December 2016) - Seo, Hyun-Woo; Seo, Jin-Kyu; Yang, Han-Sul
Abstract Background Plasma protein hydrolysates have been shown to possess antioxidant activity. However, no report has yet to examine the antioxidant effects of injection of plasma protein hydrolysates on meat quality. Therefore, in this study, the effects of injection of hydrolysis plasma protein solution on meat quality and storability were investigated in porcineM. longissimus lumborum . Methods Twelve pigs were randomly selected at a commercial slaughter plant and harvested. Dissected loins were injected with one of five solutions: C- control (untreated), T1- 10 mM phosphate buffer solution (PBS), T2- 10 mM PBS with 0.01 % butylated hydroxytoluene, T3- 10 mM PBS with 5 % plasma proteins, and T4- 10 mM PBS with 5 % hydrolysis plasma proteins. Results T3 and T4 induced greater reduction in protein content of the loin muscle than other treatments. T2 resulted in the lowest pH as well as highest cooking loss. After a storage period of 3-7 days, both lightness and redness of meat were unaffected by all injection treatments. However, yellowness was significantly elevated by treatment with T4 relative to the control. T4 also resulted in the lowest shear force (a measure of meat toughness), suggesting improvement of texture or tenderness. Further, T4 resulted in the most stable TBARS values during storage, indicating that this treatment might retard rancidity in meat. Conclusion Injection of porcineM. longissimus lumborum with hydrolysis plasma protein solution could improve overall pork quality, including tenderness and storability.